1971
DOI: 10.1002/pssb.2220440126
|View full text |Cite
|
Sign up to set email alerts
|

Optical and transport properties of the magnetic semiconductor α‐RuCl3

Abstract: The optical and transport properties in the paramagnetic phase of a-RuC1, are studied here for the first time. Values are reported for the dc conductivity of single crystals over the temperature range 110 to 500 OK in the two crystallographic directions, along and perpendicular to the optic c-axis: at 300 OK, ellc = 8 x 10' Rcm and e l c = 1.7 x 108 Rcm. The activation energy for both directions is = 0.1 eV below 300 OK and = 0.5 eV for temperatures above 400 OK. Detailed absorption spectra in the energy range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
59
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 15 publications
10
59
0
Order By: Relevance
“…However, in RuCl 3 delocalized, intersite charge excitations are located at significantly higher energies (above 0.9 eV), as described in the latter part of our manuscript. Further evidence for this point is provided by photoconductivity measurements, which show a strong onset (indicating delocalized states) near 1 eV [22]. We therefore believe that A 0 and the sharp RIXS feature do not share a common origin and that A 0 instead cor- responds to the onsite SO exciton.…”
Section: +mentioning
confidence: 84%
“…However, in RuCl 3 delocalized, intersite charge excitations are located at significantly higher energies (above 0.9 eV), as described in the latter part of our manuscript. Further evidence for this point is provided by photoconductivity measurements, which show a strong onset (indicating delocalized states) near 1 eV [22]. We therefore believe that A 0 and the sharp RIXS feature do not share a common origin and that A 0 instead cor- responds to the onsite SO exciton.…”
Section: +mentioning
confidence: 84%
“…RuCl 3 has been known for a long time and is even of some importance as a chemical [10]. Its electronic structure has been repeatedly investigated over the years by optical spectroscopy and photoemission [11][12][13]. The picture of a Mott-insulating state was proposed where the Ru 4d bands are situated close to E F but show little dispersion [13].…”
mentioning
confidence: 99%
“…Initially labeled as a semiconductor with a small gap of 0.3 eV [16], it was later discussed as a Mott-insulator [17] in which spin-orbit coupling plays a critical role [18]. A number of experimental studies with very different techniques have revealed a rich and intriguing paradigm of magnetism in this system [19-23, 25, 26].…”
mentioning
confidence: 99%